2007
DOI: 10.1101/gr.5651507
|View full text |Cite
|
Sign up to set email alerts
|

AT-rich repeats associated with chromosome 22q11.2 rearrangement disorders shape human genome architecture on Yq12

Abstract: Low copy repeats (LCRs; segmental duplications) constitute ∼5% of the sequenced human genome. Nonallelic homologous recombination events between LCRs during meiosis can lead to chromosomal rearrangements responsible for many genomic disorders. The 22q11.2 region is susceptible to recurrent and nonrecurrent deletions, duplications as well as translocations that are mediated by LCRs termed LCR22s. One particular DNA structural element, a palindromic AT-rich repeat (PATRR) present within LCR22-3a, is responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 58 publications
1
32
0
1
Order By: Relevance
“…These data suggest that translocations at PATRRs in germ cells and deletions in somatic cells occur through separate mechanisms. PATRRs 11 and 22 are both associated with non‐recurrent translocations as well, and have been proposed to play a role in genome evolution …”
Section: Types Of Secondary Structures and Links To Fork Stalling Andmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that translocations at PATRRs in germ cells and deletions in somatic cells occur through separate mechanisms. PATRRs 11 and 22 are both associated with non‐recurrent translocations as well, and have been proposed to play a role in genome evolution …”
Section: Types Of Secondary Structures and Links To Fork Stalling Andmentioning
confidence: 99%
“…PATRRs 11 and 22 are both associated with non-recurrent translocations as well, and have been proposed to play a role in genome evolution. 108 IRs are two sequences with complementary DNA on the same strand that are facing toward one another across a center of symmetry ( Figure 2). Note that many dinucleotide repeats are also IRs.…”
Section: Expansions Of Cgg Tnrs Cause Fragile X Syndrome and Fraxementioning
confidence: 99%
“…On 22q11.2, HSAT I/Alu/AT-rich regions are common and have altered the structure of the genome during evolution, leading to instability [Babcock et al, 2007]. Thus, it may play an important role in mediating translocations during meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…without an IR sequence. It could only be suggested that in this particular case an interchromatid crossing-over took place within sequences which could potentially constitute translocation ‘hot spots’, as for example are chromosomal subtelomeric regions (Babcock et al, 2007; Kirsch et al, 2008; Linardopoulou et al, 2005; Rosser et al, 2009). …”
Section: Discussionmentioning
confidence: 99%